Uncommon pair: tonsillar carcinoma and Abrikossoff tumor—case report and review - Valentini, Filippo; Messineo, Daniela; Riminucci, Mara; Corsi, Alessandro; De Virgilio, Armando (Frontiers in Oncology, 2025)
Lymphoepithelial carcinoma (LEC) is a rare malignancy within the head and neck region, histologically akin to undifferentiated nasopharyngeal carcinoma. It is uncommon outside the nasopharynx, particularly in the oropharynx and salivary glands. Granular cell tumors (GCTs), or Abrikossoff’s tumors, are rare mesenchymal neoplasms of neural origin, frequently benign but with the potential for malignant transformation. This case report presents an unprecedented clinical scenario of a 62-year-old female patient diagnosed with an HPV/EBV-negative LEC of the right palatine tonsil, coupled with metachronous squamous dysplasia and a contralateral GCT of the true vocal cord. Following initial presentation with cervical swelling, hoarseness, and dysphagia, diagnostic imaging and histopathological analyses confirmed the distinct co-occurrence of these rare entities. The patient underwent multidisciplinary treatment, including transoral robotic surgery (TORS), radical neck dissection, and adjuvant chemoradiotherapy for LEC. Simultaneously, the GCT was managed surgically with close-margin excision, with ongoing surveillance for recurrence. A comprehensive treatment strategy meticulously addressed the unique pathological and therapeutic challenges posed by the simultaneous management of these neoplasms. This case underscores the critical importance of thorough diagnostic evaluation and multidisciplinary planning in managing complex oncological scenarios. The concurrent presentation of LEC and GCT in the head and neck region necessitates individualized approaches, integrating surgical precision and adjuvant therapies. The rarity of this co-occurrence highlights the need for further studies to refine diagnostic markers and therapeutic guidelines, improving patient outcomes.